The impact of host and therapy mediated selection on HIV-1 evolution - Huang, K (2010)
The Human immunodeficiency virus (HIV) pandemic has resulted in a heavy global disease burden, and clinically causes Acquired Immuno-Deficiency Syndrome (AIDS). The development of highly active antiretroviral therapy (HAART) has achieved remarkable control of the rapidly evolving HIV. However, HIV remains neither curable nor preventable by vaccine, and in the developing regions worst affected by HIV, HAART remains inaccessible to most patients. Furthermore, the change in both immunology and viral evolution during chronic HIV infection and its relation to AIDS pathogenesis remains unknown. Following the failure of recent HIV vaccines, it is believed that a better understanding of host-pathogen interaction is vital to advance therapeutic (vaccine and drug) design. In this thesis, I have performed an investigation of viral adaptation in response to different selection forces during advanced HIV infection and AIDS. The thesis first examined a case study that reveals the potential role of B cell-mediated neutralising antibody (NAb) in chronic HIV infection through the unexpected effect of B cell depletion agent, anti-CD20 (Rituximab). Here, longitudinal results have shown that viral load (VL), env gene diversity, and NAb sensitive strains increased during B cell and NAb depletion as a result of Rituximab administration, and reversed as B cells recovered. The study provides preliminary evidence to support the idea that NAb may be effective at suppressing HIV. The rest of the thesis focused on the cross-sectional cohort at Bloemfontein, South Africa (n=1491), a resource-limited region affected by the pandemic. Here, we used methods that include molecular and pretherapy drug resistance epidemiology, mathematical modelling, phylogenetically adjusted bioinformatics analysis and in vitro viral replication capacity (VRC) assay to study materials including cohort demography, plasma samples, CD4 cell count, VL, viral genetic sequences and host human leukocyte antigen (HLA) tissue types. Our analysis was further augmented by the additional data kindly contributed by our neighbouring Durban cohort collaborators (n=775), which also includes an IFN! ELISPOT assay that measures cytotoxic T lymphocyte (CTL) responses. Using the HIV pol sequencing data and phylogenetic analysis we confirmed that the local molecular epidemiology is similar to the circulating strains documented in the regional database. However, the pretherapy drug resistance mutation screening results have revealed an unexpected high incidence of drug-induced viral mutants in the AIDS patients with CD4 counts <100 cells/μl. According to mathematical modelling, this finding is attributable to additional sources of antiretroviral therapy exposure, which warrants public health caution. The investigation then focused on studying the changes in HLA class I mediated CTL selection and viral evolution as CD4 counts are reduced in AIDS. Interestingly we have noted evidence that suggest weakening CTL immune selection against gag during AIDS is associated with increased viral fitness (measured by VRC) and reversion of previous immune-escape mutations which conferred high fitness costs. In conclusion, this thesis compared different sources of host and drug mediated HIV selection and its implication for viral evolution. The identification of more bottleneck sites conferring high fitness costs to the selection of escape mutants is expected to be helpful in the design of future therapeutics (via vaccine, drug, immune therapy, or public health strategy). As we have learnt from the principle of combinational ARV, it would be desirable for a vaccine to select HIV at multiple sites of high escape-mutation fitness cost, hence offering protective effect.